Tanshinol borneol ester on nanostructured lipid carriers has longer brain and systemic effector retention and better antioxidant activity in vivo - Yuan X (Dove Medical Press, 2018)
Xinyi Yuan, Fuhuan Fei, Huanmei Sun, Chaoni Xiao, Xinfeng Zhao, Yajun Zhang, Xiaohui Zheng Key Laboratory of Resource Biology and Biotechnology in Western China, Ministry of Education, College of Life Sciences, Northwest University, Xi’an, People’s Republic of China Background: Tanshinol borneol ester (DBZ) is a hybrid of danshensu (DSS) and borneol and has anti-ischemic activity in animals. However, its low water solubility and short half-life limit its clinical application. Methods: We prepared polyethylene glycol (PEG)-modified and DBZ-loaded nanostructured lipid carriers (DBZ-PEG-NLC) and DBZ-NLC, and examined their physical characteristics, such as particle size, zeta potential, entrapment efficiency and drug loading. The in vitro stability and pharmacokinetics in rats as well as antioxidant activity of DBZ-PEG-NLC and DBZ-NLC in a C57BL/6 mouse model of ischemia/reperfusion-related brain injury were investigated. The levels of DBZ and its hydrolyzed DSS in rat plasma and brain microdialysates were determined by liquid chromatography–mass spectroscopy/mass spectroscopy analysis. Results: We found that the mean particle size and entrapment efficacy of DBZ-PEG-NLC were similar to that of DBZ-NLC. The DBZ-PEG-NLC, like DBZ-NLC, released DBZ in a biphasic manner with initially burst release and then prolonged slow release in vitro. Intravenous injection of DBZ-PEG-NLC resulted in significantly higher levels and longer retention periods of DBZ and DSS in plasma and the brains than DBZ-NLC and DBZ in rats. Finally, treatment with DBZ-PEG-NLC achieved a better antioxidant activity than DBZ or DBZ-NLC in mouse model of ischemia/reperfusion by reducing the levels of brain malondialdehyde, but increasing the levels of brain superoxide dismutase and glutathione. Conclusion: DBZ-PEG-NLC is a preferable option to deliver DBZ for sustainable release of DSS and borneol in vivo, and may serve as a promising drug for effective therapy of ischemic cardiovascular and cerebrovascular diseases. Keywords: nanovesicles, pharmacokinetics, brain microdialysis, ischemic cerebrovascular diseases, polyethylene glycol, danshensu